新移民女性的敘事文本及其教育意涵 The Narrative Texts of New Female Immigrants and Their Implications in Education - 王碧霜 Wang, Pi-Shuang; 黃淑玲 Huang, Shu-Ling (National Changhua University of Education, 2009)
新移民的移入是一個多元文化社會不可避免的現象。大量新移民女性藉由跨國 婚姻而移入台灣，造成台灣社會的不安與恐慌，這樣的恐慌源自於新移民女性的人 口數迅速竄升、其所處的性別弱勢，以及台灣社會對於第三世界移民所抱持的主流 意識型態。學術界對於新移民的研究多如牛毛，也針對各項議題提出建言，並促使 國家社會開始重視新移民女性的基本權益。在諸多研究中，有不少研究採用質性訪 談的方式，蒐集新移民女性的口述文本作為分析對象。本文主張，若能集結這些新 移民女性的敘事文本，作為案例應用於教育上，將可促進台灣的多元文化教育。因 此，本文首先闡述敘事文本的意義與閱讀詮釋的功能，並論述發展敘事文本可以作 為台灣新移民女性的發聲管道，與閱讀新移民女性的敘事文本可以作為觀念轉化的 媒介，接著分析新移民女性敘事文本的部分內容，最後提出新移民女性的敘事文本 在教育應用上的意義與結論。 It is an unavoidable phenomenon that many immigrants are in a multicultural society. A large number of new female immigrants move into Taiwan through transnational marriage make the uneasiness and fear of the society in Taiwan. Such fear stems from that we don't really understand the new female immigrants and their culture, most of us are biased to them. There are many inquiry studies about new female immigrants and there are many new female immigrants' narrative texts in these studies. If the narrative texts can be used as cases in education, it will improve the multicultural education in Taiwan. In this paper, first we describe the meaning and functions of a narrative text. Then, we have some reasons why a narrative text could be a way for woman to voice and why the narrative texts of new female immigrants could make us more understand different cultures, so we may treat them equally. Third, we try to analyze some examples of narrative texts of new female immigrants from other studies. Finally, we address some implications of the narrative texts used as cases in education.